Exploring Equity in Higher Education Systems: Reflections from Argentina and Chile - García de Fanelli, Ana (International Higher Education, 2019)
Given the complexities of massification and institutional differentiation in higher education, it is not possible to analyze the equity of a system by focusing only on the global policies regulating access and state or private funding mechanisms. When focusing on secondary school and undergraduate dropout rates and on the programs and institutions that lower-income students can attend, striking inequalities may appear.